Radiotherapy improves the clinical outcomes of recurrent or metastatic head and neck cancers treated with immunotherapy - Yanshuang Cheng; Juan Wang; Ji Sun; Yahua Zhong; Qiuji Wu (Discover Oncology)
Abstract Background It is uncertain whether the combination of immunotherapy and radiotherapy can provide survival benefits for recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC). Methods We retrospectively analyzed the impact of radiotherapy on the efficacy of immunotherapy and prognostic analysis in 113 patients with R/M HNSCC in our institution from 2018 to 2022. The Kaplan–Meier method was utilized for survival analysis, and Cox regression analysis was conducted to identify prognostic factors. Results The median follow-up time was 14.0 months. During immunotherapy, 37 patients received radiotherapy, targeting primary tumors, lymph nodes, metastasis in liver, lung, bone, and other sites. We found that the group receiving immunotherapy combined with radiotherapy had higher objective response rate (67.6% vs 39.5%, p = 0.009) and disease control rate (94.6% vs 61.8%, p = 0.001) than those without radiotherapy. The median progression-free survival (20.0 months vs 4.0 months, p = 0.00098) and overall survival (not reached vs 26.0 months, p = 0.006) were improved in patients receiving radiotherapy compared to those not. Conclusions The combination of immunotherapy and radiotherapy demonstrates improved clinical outcomes in R/M HNSCC.